THE ZEOLITE-CONTAINING MINERAL SUPPLEMENT BASALTIC TUFF AND ITS IMPACT ON THE PRODUCTIVE PERFORMANCE OF TURKEYS FOR FATTENING - Овчаров, О. В.; Косташ, В. Б.; Шутяк, О. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The results of studies on the influence of mineral additives tseolitcontaining basalt tuff in live weight and average daily gain of fattening turkeys. Established that the safety of turkeys for the entireresearch period was quite high in all groups. It observed that the higher the percentage of input Product turkey feeding the diet, the higher their weight. At 3 months of age turkey control, 1st, 2nd and 3rd experimental group increased live weight of under 3,28 times, 3,50; 3,72 and 3,63 times compared with weight lectern in the formation of groups. Before the slaughter at the age of 24 weeks turkey control group had a live weight of 14,86 kg. Live weight sverstnykov1st, 2nd and 3rd experimental groups was respectively 0,82 kg or 5,2%; at 1,59 kg or 10,7% and 1,03 kg or 6,9% more than in the control group counterparts. Analysis of average daily increases shows that poultry research comparedwith controls (151,2) dominated by increments respectively: 1-st – 160,0 research; 2-nd – 170,1; 3-rd – 164,0h. and by live weight (14,95 versus the control groups in research: 15,68; 16,45; 15,89 kg). The highest average daily increases in body weight and at the least cost feed both the growing period and during the whole period of the experiment, were obtained in the 2nd experimental group. Compared with the control group live weight of turkey poults in that group was higher at 8,8; 37,6 and 85,4 grams or 3,1; 2,5 and 3,1%, where dose supplements in the diet tseolitovmisnohocontaining basalt tuff was 2 kg/t.